2022
DOI: 10.3389/fendo.2022.880002
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin and Endothelin Receptor Structures With Implications for Signaling Regulation and Pharmacological Targeting

Abstract: In conjunction with the endothelin (ET) type A (ETAR) and type B (ETBR) receptors, angiotensin (AT) type 1 (AT1R) and type 2 (AT2R) receptors, are peptide-binding class A G-protein-coupled receptors (GPCRs) acting in a physiologically overlapping context. Angiotensin receptors (ATRs) are involved in regulating cell proliferation, as well as cardiovascular, renal, neurological, and endothelial functions. They are important therapeutic targets for several diseases or pathological conditions, such as hypertrophy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…With the help of MD simulations, the four most reasonable mutual interfaces have been proposed: symmetric TM1,2,8, TM5, TM4, and TM4,5 [ 103 ]. The only report on AT1R homodimer structure (PDB ID: 6do1) indicates that the interface between individual protomers consists of hydrophobic and aromatic amino acid side chain contacts at ECL1, TM1, TM2, TM3, and H8 [ 104 ] (Fig. 4 E).…”
Section: The Future Of Drug Design Based On At1r: Finding the Alloste...mentioning
confidence: 99%
“…With the help of MD simulations, the four most reasonable mutual interfaces have been proposed: symmetric TM1,2,8, TM5, TM4, and TM4,5 [ 103 ]. The only report on AT1R homodimer structure (PDB ID: 6do1) indicates that the interface between individual protomers consists of hydrophobic and aromatic amino acid side chain contacts at ECL1, TM1, TM2, TM3, and H8 [ 104 ] (Fig. 4 E).…”
Section: The Future Of Drug Design Based On At1r: Finding the Alloste...mentioning
confidence: 99%
“…Ang II can stimulate the release of immunoreactive ET from rat vascular smooth muscle cells via the AT1 receptor. Moreover, it shares a common receptor–effector transduction pathway with ET, and the two may promote vascular smooth muscle cell growth through a common intracellular signaling mechanism [ 67 , 68 ]. Its activity is potentiated by growth factors such as PDGF, epidermal growth factor (EGF), basic FGF, TGF-α, TGF-β, and insulin-like growth factor to synergistically stimulate DNA synthesis in vascular smooth muscle cells, fibroblasts, mesangial cells, melanocytes, osteoblasts, and ECs [ 60 , 69 , 70 ].…”
Section: Endothelin Receptors and Their Pathway Mechanismsmentioning
confidence: 99%
“…Here, anti-GPCR-directed RABs associated with allograft vasculopathy constitute a distinct phenotype of antibody-mediated rejection (ABMR) ( 9 , 10 ). After establishing the functional role of RABs directed against the angiotensin II type 1 receptor (AT1R) and endothelin receptor type A (ETAR) for vascular integrity and graft function/survival in the KTx setting ( 4 , 8 , 9 , 11 16 ), subsequent studies have identified several RABs directed against GPCR targets typically associated with the vasculature, such as protease-activated receptors (PARs), neuronal and chemokine receptors, and the levels of these RABs are often modulated with patient age and disease status ( 1 , 17 , 18 ). Vasculature-associated RAB targets can be found on different types of micro-/macro-vascular endothelial cells (ECs), vascular smooth muscle cells (VSCMs), and perivascular multipotent mesenchymal stromal/stem cells (MSCs), but also neuronal cells, which are all often employed as model systems to study respective molecular signaling mechanisms ( 1 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%